2021
DOI: 10.1038/s41430-021-01024-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chronotype and social jetlag during adolescence and their association with concurrent changes in BMI-SDS and body composition, in the DONALD Study

Abstract: Background/objectives Adolescence is a critical period for both the development of overweight and the transition toward a later chronotype, often accompanied by an increase in social jetlag. This study assessed whether changes in chronotype and social jetlag, are linked to changes in body composition during adolescence. Subjects/methods We used data from the DONALD open cohort study, collected between 2014 and 2019, from 213 adolescents (9–17 years at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 53 publications
2
27
1
Order By: Relevance
“…At present, we do not know whether these differences are involved in real-life scenarios or not. Follow-up of 2.1 years delayed 40 min of MSFsc in adolescence, and delta MSFsc was positively associated with Fat-Free Mass index [ 39 ]. Thus, 0.7–1.1 h differences in MSFsc in the present research may be related to muscle function.…”
Section: Discussionmentioning
confidence: 99%
“…At present, we do not know whether these differences are involved in real-life scenarios or not. Follow-up of 2.1 years delayed 40 min of MSFsc in adolescence, and delta MSFsc was positively associated with Fat-Free Mass index [ 39 ]. Thus, 0.7–1.1 h differences in MSFsc in the present research may be related to muscle function.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, almost all included studies were cross-sectional, making it impossible to assess the cause and effect of the observed associations. However, of the few prospective studies that were included, two showed that social jetlag was associated with more weight gain (Jankovic et al, 2022;Kim et al, 2020) and one showed larger fasting glucose and triglycerides levels over a 1-year follow up in people with T2D and social jetlag (Mota et al, 2021). One study showed no significant associations between social jetlag and change in BMI and waist circumference (de Zwart et al, 2018), which is possibly due to differences in age of the study population, with the former being in a teenage population compared to adult populations in the first studies.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Normal healthy adolescents (9–17 years) have an average mid‐sleep time of 3:30 a.m 34 . Adolescent patients living with SCD in our study experience a later mid‐sleep time (4:15 a.m.).…”
Section: Discussionmentioning
confidence: 61%